Disliked and demonized dollies: pediophobia and popular toys of the present - Heljakka K (My University, 2022)
This study explores the phenomenon of pediophobia and popular character toys of the present day. Pediophobia, or, the fear of dolls, is a common reaction when discussing character toys with adults. By turning to a combination of various research materials concerned with popular toys, their characteristics, and the audiences who dislike and dismiss them such as previous research papers, media texts and interviews with adult toy players, my aim is to locate the joint phenomenon of the disliked ‘dollies’ and pediophobia in popular culture, the currently communicated reasons for it, and the strategies for avoiding encounters with the ‘dislikeys’.